A European Union and Canadian Review of Public Health Nursing Preparation and Practice. Issue 1 (5th October 2012) - Hemingway, Ann; Aarts, Clara; Koskinen, Liisa; Campbell, Barbara; Chassé, France
Abstract Objective This study explores the preparation and role of the public health nurse (PHN) across European Union (EU) countries (Finland, Sweden, and the United Kingdom) and Canadian provinces (Alberta, New Brunswick, and Prince Edward Island). Methods A literature review including relevant peer reviewed articles from 2000 on, in conjunction, with critical debate was undertaken. The results were considered in relation to the three essential areas of PHN practice, outlined in the World Health Organization (Moving on from Munich: A reference guide to the implementation of the declaration on nurses and midwives: A force for health, 2001b) recommendations, family oriented care, public health action, and policy making. Results The major challenge the review revealed across a variety of international education and practice environments was the lack of consistent preparation for and engagement with leadership and policy making in practice.